2D Silicon Magnetometer. (2016) - Lozanova, S.V.; Noykov, S.A.; Roumenin, Ch.S.
Abstract: A novel single-chip sensing device for measurement of two orthogonal magnetic-field components using one and the same transducer zone is presented. On a rectangular n -type silicon substrate, four n + - ohmic planar contacts are implemented – two of them are elongated and serves as power supply, and other two terminals positioned in the middle of the region between elongated ones, function as outputs only. A proper coupling arrangement is used for obtaining the information about vector components B x (parallel to the supply contacts) and B z (perpendicular to the substrate). The sensor operation is determined by the direction of individual parts of the curvilinear current trajectory and the Lorentz force action on them. The 2D magnetometer interface circuitry comprises three instrumentation amplifiers and a differential amplifier. Simple fabrication technology is applied. The effective spatial resolution is high consisting 90 x 60 x 40 μm 3 . The respective channel-magnetosensitivities without amplification reaches Sx ≈ 17 V/AT and Sz ≈ 23.3 V/AT, the channel cross-talk at induction B ≤ 1.0 T is no more than 3% and lowest detected induction B min for the two-axis device at a supply 3 mA over frequency range f ≤ 100 Hz is about 11 μT.